2013
DOI: 10.1111/gtc.12105
|View full text |Cite
|
Sign up to set email alerts
|

Oligo‐astheno‐teratozoospermia in mice lacking ORP4, a sterol‐binding protein in the OSBP‐related protein family

Abstract: Oligo-astheno-teratozoospermia (OAT), a condition that includes low sperm number, low sperm motility and abnormal sperm morphology, is the commonest cause of male infertility. Because genetic analysis is frequently impeded by the infertility phenotype, the genetic basis of many of OAT conditions has been hard to verify. Here, we show that deficiency of ORP4, a sterol-binding protein in the oxysterol-binding protein (OSBP)-related protein family, causes male infertility due to severe OAT in mice. In ORP4-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…A recent report that ORP4 knock-out mice are normal except for male infertility indicates that ORP4 has an essential function in tissues where it is highly expressed. In this case, lack of ORP4 resulted in apoptosis of postmeiotic spermatids and defects in germ cell differentiation (31). ORP4 could have an essential sterol and/or PI-4P transfer or sensing activity that has been re-established in immortalized and transformed cells to provide a growth advantage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent report that ORP4 knock-out mice are normal except for male infertility indicates that ORP4 has an essential function in tissues where it is highly expressed. In this case, lack of ORP4 resulted in apoptosis of postmeiotic spermatids and defects in germ cell differentiation (31). ORP4 could have an essential sterol and/or PI-4P transfer or sensing activity that has been re-established in immortalized and transformed cells to provide a growth advantage.…”
Section: Discussionmentioning
confidence: 96%
“…ORP4 is highly expressed in testis and, to a lesser extent, in brain and heart but is virtually absent from other human and mouse tissues (18,31). A recent report that ORP4 knock-out mice are normal except for male infertility indicates that ORP4 has an essential function in tissues where it is highly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, ORP4L deficiency did not affect the ability of macrophages to take up uncoated or ox-LDL-coated FluoSphere beads ( Figure 1D, middle) nor did it affect the engulfment of anti-Fas antibody-induced apoptotic Jurkat T cells ( Figure 1D, right). As ORP4 deletion has been reported to increase sperm apoptosis, 31 we next examined whether ORP4L modulates macrophage apoptosis. When compared with cells from WT mice, a significant increase in macrophage apoptosis was detected in preparations from ORP4L −/− mice ( Figure 1E).…”
Section: Orp4l Is Expressed In Macrophages and Protects Them From Apomentioning
confidence: 99%
“…[23][24][25][26] Certain ORPs bind and transport oxysterols, cholesterol, and phosphoinositides. [27][28][29] ORP4 (also known as oxysterol-binding protein 2) has been reported to bind oxysterols; it is expressed constitutively in brain, heart, and testis 30,31 and is present as 3 major variants, oxysterol-binding protein-related protein 4 L (ORP4L), ORP4M, and ORP4S. 30,32 Early studies reported that ORP4L was detectable in peripheral blood leukocytes from patients with chronic myeloid leukemia, but not from healthy donors.…”
mentioning
confidence: 99%
See 1 more Smart Citation